Menace of antimicrobial resistance in LMICs: Current surveillance practices and control measures to tackle hostility. Issue 2 (February 2022) - Sharma, Ayush; Singh, Akanksha; Dar, Mukhtar Ahmad; Kaur, Rimple Jeet; Charan, Jaykaran; Iskandar, Katia; Haque, Mainul; Murti, Krishna; Ravichandiran, V.; Dhingra, Sameer
Abstract: Antimicrobial Resistance (AMR) is significant challenge humanity faces today, with many patients losing their lives every year due to AMR. It is more widespread and has shown a higher prevalence in low- and middle-income countries (LMICs) due to lack of awareness and other associated reasons. WHO has suggested some crucial guidelines and specific strategies such as antimicrobial stewardship programs taken at the institutional level to combat AMR. Creating awareness at the grassroots level can help to reduce the AMR and promote safe and effective use of antimicrobials. Control strategies in curbing AMR also comprise hygiene and sanitation as microbes travel from contaminated surroundings to the human body surface. As resistance to multiple drugs increases, vaccines can play a significant role in curbing the menace of AMR. This article summarizes the current surveillance practices and applied control measures to tackle the hostility in these countries with particular reference to the role of antimicrobial stewardship programs and the responsibilities of regulatory authorities in managing the situation.